Early single centre experience of flow diverting stents for the treatment of cerebral aneurysms. (October 2013) - Toma, Ahmed K.; Robertson, Fergus; Wong, Ken; Joshi, Yogish; Haridas, Avinash; Grieve, Joan; Watkins, Laurence D.; Kitchen, Neil D.; Brew, Stefan
Abstract Introduction. The flow diverting stent (FDS) is a relatively new endovascular therapeutic tool specifically designed to reconstruct the parent artery and divert blood flow along the normal anatomical course and away from the aneurysm neck and dome. Methods. Retrospective review of prospectively built clinical and imaging database of patients treated with FDS at the National Hospital for Neurology and Neurosurgery, Queen Square, London, UK was done. Results. Between 18/03/2008 and 10/11/2011, 80 patients underwent 84 FDS insertion procedures for various indications. Mean duration of clinical follow-up was 11.3 ± 9.3 months and of imaging follow-up was 10.6 ± 9.3 months. Sixty-seven had anterior circulation aneurysms while 17 had posterior circulation aneurysms. Seven (8.3%) patients died (two probably not related, giving a procedure-related mortality of 5.9%), eight had permanent new deficit (9.5%), 20 had transient deficit (23%) and 49 (58%) had no complications. There was a trend towards bad outcome with larger posterior circulation aneurysms. Angiographic follow-up showed 38% cure rate at 6 months and 61% at 12 months. Conclusion. FDS should only be used following multidisciplinary discussion in selected patients. Further data is required regarding long-term safety, efficacy and indications.